2021
DOI: 10.1055/a-1390-4353
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Replacement Therapy After Gynaecological Malignancies: a Review Article

Abstract: Rapid advances in oncology have led to an increased survival rate in cancer patients, who live long enough to reach the natural age of menopause or experience the end of gonadal function as a side effect of oncological treatment. Survivors after gynaecological malignancies are a major challenge as these diseases are hormone-dependent and hormone replacement therapy (HRT) possibly increases the risk of recurrence. This article is based on a selective literature search for relevant studies and guidelines regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…We observed that MSH2 is not closely related to BMI, although obesity is a main risk factor for endometrial cancer (Kliemann et al, 2021;Sourouni & Kiesel, 2021). Age is another risk factor for endometrial cancer, and MSH2 expression is related to age (Chatsirisupachai et al, 2021;Deshpande et al, 2020).…”
Section: Discussionmentioning
confidence: 71%
“…We observed that MSH2 is not closely related to BMI, although obesity is a main risk factor for endometrial cancer (Kliemann et al, 2021;Sourouni & Kiesel, 2021). Age is another risk factor for endometrial cancer, and MSH2 expression is related to age (Chatsirisupachai et al, 2021;Deshpande et al, 2020).…”
Section: Discussionmentioning
confidence: 71%
“…Continuous endometrial exposure to oestrogens increases the risk of endometrial hyperplasia and cancer, but adding progestogen has a protective role. However, there is a lack of research on HT regarding endometrial cancer [36]. Furthermore, no consensus has been achieved on the best progestogen, dosage, administration method, therapy duration, and the follow-up protocol [37].…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Patients suffering from breast cancer who develop menopausal symptoms pose a major challenge as HRT may increase the risk of recurrence. The data for this are insufficient to derive a standardized procedure [6]. Individual advice is of particular importance in this case.…”
Section: Introductionmentioning
confidence: 99%